Conceptual design and thermodynamic assessment of an integrated sCO2 Waste-Heat recovery system for sustainable co-generation of ammonia - Hamza Ahmed; Tariq Talha; Muhammad Shoaib Ahmed Khan; Usama Perwez; Abdur Rehman Mazhar; Muhammad Rehan Khan; Talha Irfan Khan (Fuel, 2027)

Retraction Note: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2026)

Synthesis, Characterization and Antibacterial Activity of DEAE-C Loaded Cefixime Nano-Particles Against Resistant Bacterial Strains - Muhammad Tayyub Kazam; Saman Arooj; Mahpara Tabassum; Hamid Saeed; Mehwish Iqtedar; Nadeem Ahmad; Muhammad Islam; Muhammad Fawad Rasool; Muhammad Usama; Aleena Maryam (Journal of Pharmaceutical Innovation, 2026)

Comparative Analysis of Polymeric and Lipid Polymer Hybrid Nanoparticles: In-Vitro and In-Vivo Analysis for Pulmonary Delivery of Atorvastatin - Kifayat Ullah Shah; Muhammad Usama Ghani Khan; Fahad Y. Sabei; Muhammad Danish Saeed; Firdous Ahmad Burki; Muhammad Yasir Ghani Khan; Awaji Y. Safhi; Ahmad Salawi; Abdullah Alsalhi; Ali Hanbashi (Journal of Pharmaceutical Innovation, 2026)

Protective effects of Coagulansin-A against LPS-induced inflammatory and oxidative stress responses in human lung epithelial cells - Sadaf Naz; Umakant Yadav; Sidra Faiz; Muhammad Usama Mazhar; Syeda Rida Zainab; Rizwan Ul Haq; Fadi Khasawneh; Ihsan Ul Haq; Muhammad Khalid Tipu; Lin Zhu (Toxicon, 2026)

Viscosity-driven rapid photopolymerization of UHMW-PMMA/SBS: synergistic energy dissipation for high-temperature resistant ballistic adhesives - Tianhong Dong; Muhammad Usama; Cheng Yan; Dayong Lin; Xinpeng Wang; Jianyong Yu; Shuohan Huang; Yong He (Chemical Engineering Journal, 2026)

Integrative Network Pharmacology and Molecular Dynamics Simulation Uncover Key Molecular Targets of Curcumin and Its Derivatives in Colorectal Cancer - Usama Ilahi; Muhammad Suleman; Abrar Mohammad Sayaf; Muhammad Rizwan; Fazal Akbar; Zafar Ali; Haji Khan; Zahid Hussain; Mohammad Ali; Hadi M. Yassine; Abdullah A. Shaito; Sergio Crovella (Journal of Pharmaceutical Innovation, 2026)

Lornoxicam Loaded Transethosomal Gel: Formulation, Box-Behnken Optimization, Ex-Vivo and In-Vivo Characterization - Minahal Munir; Sarah Ahmad; Talha Jamshaid; Huma Hameed; Muhammad Zaman; Usama Jamshaid; Muhammad Jamshaid; Sara Khalid; Heba A. Gad (Journal of Pharmaceutical Innovation, 2026)

Retraction Note: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2026)

Molecular mechanisms and integrated breeding strategies for durable resistance to rice blast and other major pathogens - Daud Ali Shah; Muhammad Usama Younas; Zameer Hussain Jamali; Usman Zulfiqar; Mohammed S. Alotaibi; Mayank Anand Gururani; Owais Iqbal (Physiological and Molecular Plant Pathology, 2026)

Experimental evaluation of porosity-induced performance enhancement in intermittent microwave drying of carrot slices - Muhammad Usama; Zaib Ali; Macmanus C. Ndukwu; Waseem Mushtaq; Aashir Iqbal; Tahmid Hassan Rupam (Food and Bioproducts Processing, 2026)

Multi-omics and precision breeding strategies for enhancing biotic and abiotic stress resilience in rice - Zameer Hussain Jamali; Muhammad Usama Younas; Muhammad Qasim; Sajad Ali; Rashid Iqbal; Saltanat Aghayeva; Petr Konvalina (Cereal Research Communications, 2026)

Disrupting virulence: in silico discovery of MexL inhibitors to block pyocyanin biosynthesis in Pseudomonas aeruginosa - Usama Bin Asghar; Irfa Asghar; Samavia Akhter; Muhammad Ibrash Khan; Syeda Zurriat Fatima; Tatheer Alam Naqvi; Maria Kanwal Ali; Raza Ahmad; Muhammad Ali (Archives of Microbiology, 2026)

Returning straw and applying appropriate nitrogen fertilizer could increase acid-hydrolysable ammonium nitrogen and amino sugar nitrogen in the soil, thereby promoting effective panicle number and ultimately boosting rice yield - Linya Lu; Zhengli Song; Yang Hu; Liang Luo; Guiling Xu; Yuehua Feng; Muhammad Usama Latif; Somsana Phonenasay; Bingping Cui; Xiangjun Xu; Jianhua Huang; Yanni Wei (Plant and Soil, 2026)

Performance evaluation of sustainable concrete incorporating mineral fillers: experimental insights and predictive modeling using advanced machine learning - Maaz Khan; Muhammad Faisal Javed; Usama Asif; Hisham Alabduljabbar (Innovative Infrastructure Solutions, 2026)

“Ondansetron augmentation for obsessive–compulsive disorder: A systematic review and meta-analysis of randomized placebo-controlled trials” - Anas Mohammad; Mohammad Ibrahim; Aneeq Mahmood Khan; Usama Pervaiz; Sarah Aijaz; Muhammad Hassnain Nasrullah; Hammad Jamil (European Journal of Clinical Pharmacology, 2026)

RAFE-net: A robust attention-based fusion framework for classifying fish feeding behavior from sonar and acoustic data - Usama Iqbal; Daoliang Li; Muhammad Farrukh Qureshi; Zohaib Mushtaq; Hafiz Abbad Ur Rehman (Aquacultural Engineering, 2026)

Controlling surface temperature in Intermittent Microwave Drying of potato slices using evaporative cooling: An experimental study - Muhammad Usama; Zaib Ali; Aashir Iqbal; Macmanus C. Ndukwu (Innovative Food Science & Emerging Technologies, 2026)

Assessment of Coagulansin-A’s therapeutic potential and safety in an ovalbumin (OVA) induced airway inflammation model - Sadaf Naz; Muhammad Usama Mazhar; Aimen Wajid; Rimsha Noor; Lin Zhu; Muhammad Khalid Tipu (Inflammopharmacology, 2026)

Correlation of tree stem diameter with root architecture, mechanical properties, and slope stability in a mountainous Cryptomeria plantation - Mehtab Alam; Jianfeng Chen; Usama Ayub; Umar Muhammad (Journal of Mountain Science, 2026)

Petrographic and geomechanical evaluation of nikanai ghar formation (KPK) and kuldana formation (Punjab) rocks: A comparative study for their suitability as building materials in Pakistan - Hassan Ayaz; Jiancong Xu; Sohail Ahmad; Muhammad Usama Aslam (Arabian Journal of Geosciences, 2026)

Integrated physicomechanical, petrographic, and geochemical evaluation of eocene carbonate aggregates from the Salt Range, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Amir Shahzad; Yasir Sirfraz; Muhammad Tayyib Riaz; Usama Shabir Abbasi; Salman Rasheed (Innovative Infrastructure Solutions, 2026)

Retraction Note: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2026)

Mechanistic and Synergistic Evaluation of Amodiaquine–Isometamidium Combination Against Trypanosoma evansi: Integrated In Silico–In-Vitro Insights - Waqas Ahmad; Naeem Rasool; Mehmood Ahmad; Muhammad Yasin Tipu; Tehreem Fayyaz; Usama Bin Naeem; Sadaf Aroosa; Rana Muhammad Zahid Mushtaq (Acta Parasitologica, 2026)

Exploring the efficacy of a novel cannabidiol and bevacizumab combination in non-small cell lung cancer - Abdul Qadir; Zurqa Khalid; Ayesha Kashmala Ghauri; Muhammad Hamza Dawood; Usama Manzoor; Habib Ur Rehman (DARU Journal of Pharmaceutical Sciences, 2026)

Liquid organic hydrogen carriers (LOHC): from definitions to recent developments - Muhammad Usama Daud; Francesco Taddeo; Luciana Lisi; Ernesto Salzano; Martino Di Serio; Riccardo Tesser; Vincenzo Russo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Competitive adsorption of antibiotics on waste-derived hybrid biochar: Performance, mechanism, and life cycle assessment - Ali Hamid; Ahsan Jalal; Muhammad Arshad; Muhammad Usama; Sajjad Hussain; Hammad Khan (Journal of Environmental Chemical Engineering, 2026)

Effects of Melatonin on Morpho-Physiological Activity of Cotton Seedlings Under Cold and Normal Temperature - Irshad Ahmad; Guanglong Zhu; Xuebing Yan; Yanqing Wu; Muhammad Usama Younas; Guisheng Zhou (Journal of Plant Growth Regulation, 2026)

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Phenology-aware in-season crop yield estimation through UAV multispectral imagery and deep neural networks - Usama Athar; Muhammad Ali; Zuhair Zafar; Zahid Mahmood; Karsten Berns; Farid Bourennani; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2026)

Drosophila proteasome subunit Rpn8 controls IMD pathway activation via PGRP-SC2 degradation - Mingfei Wu; Umar Ali; Sen Ding; Chuchu Zhang; Yiheng Jin; Xinyan Cao; Muhammad Abdul Rehman Saeed; Yangyang Zhu; Muhammad Usama; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2025)

Genetic Mechanisms and Improvement Strategies for Rice Sheath Blight Resistance - Muhammad Usama Younas; Bisma Rao; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Saima Parveen Memon; Rashid Iqbal; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Endophyte Bacterial Metabolites: An Active Syrup for Improvement of Growth, Biomass, and Antioxidant System of Zea mays L. in Drought Condition - Mahwish Salman; Muhammad Rizwan Javed; Anam Tariq; Muhammad Usama; Hafiza Iqra Hanif; Bushra Sadia; Shazia Naheed (Journal of Plant Growth Regulation, 2025)

Diversity of arthropods fauna in correlation to abiotic factors in wheat crop - Dilbar Hussain; Bushra Khalid; Muhammad Asrar; Usama Saleem; Wafa Abdullah Hamad Alkherb; Muhammad Saleem; Hina Anwar; Saddam Hussain; Muhammad Sohail Qadir; Mubshar Saleem; Khalid Ali Khan; Hamed A. Ghramh; et al. (International Journal of Tropical Insect Science, 2025)

LightHybridNet-Transformer-FFIA: A hybrid Transformer based deep learning model for enhanced fish feeding intensity classification - Usama Iqbal; Daoliang Li; Muhammad Farrukh Qureshi; Zohaib Mushtaq; Hafiz Abbad ur Rehman (Aquacultural Engineering, 2025)

Passage performance of three small-sized fish species in a Vertical Slot Fishway with and without overhead cover - Fabio Tarena; Claudio Comoglio; Michele Spairani; Alessandro Candiotto; Muhammad Usama Ashraf; Margherita Abbà; Carlo Ruffino; Daniel Nyqvist (Ecological Engineering, 2025)

Evolving climatic patterns and drought risk in Pakistan’s agro-ecological zones - Raja Muhammad Usama; Sawaid Abbas; Mansour Almazroui; Muhammad Fahad Bilal; Asad Ali (Theoretical and Applied Climatology, 2025)

Integrated Approaches for Enhancing Magnaporthe oryzae Resistance: Mechanisms and Breeding Strategies - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Tanweer Fatah Abro; Shabir Ahmad; Xiaohong Jiang; Nimra Rajput; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Phosphorus Modified Biochar and Vermicompost Integration Alleviated Cd Phytotoxicity in Wheat (Triticum aestivum L.) by Improving Growth, Antioxidant Activities and Reducing Cd Uptake in Plants - Ahmad Ali; Zaffar Malik; Ghulam Hassan Abbasi; Muhammad Waseem; Muhammad Rizwan; Muhammad Ali; Sobia Afzal; Syed Farhan Haider Bukhari; Usama Ali Tahir (Journal of Soil Science and Plant Nutrition, 2025)

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

DusVax: a universal pan-viral multi-epitope vaccine (PV-MEV) for pandemic preparedness against ten high-priority viral pathogens - Allah Rakha Yaseen; Muhammad Suleman; Mahrukh Afzal; Hania Usama; Warda Ashfaq; Sehrish Firyal; Ayesha Arif; Amna Latif; Ali Asghar; Abdul Salam Qadri (The Nucleus, 2025)

A combined gasification-chemical looping approach for valorizing waste tires into ammonia: Techno-economic analysis - Ali A. Al-Qadri; Usama Ahmed; Hafiz Muhammad Ali; Ahmad Salam Farooqi (Waste Management, 2025)

Adsorption of 4-bromophenol from simulated wastewater using magnetic carbon-based composites: Kinetics, equilibrium, thermodynamics, and density functional theory analysis - Beatris L. Mello; Pascal S. Thue; Ali Hamid; Muhammad Usama; Fernando Machado Machado; Moaaz K. Seliem; Younes Dehmani; Glaydson S. dos Reis; Mohamed Abdel Salam; Hammad Khan; Luis F.O. Silva; Eder C. Lima (Journal of Water Process Engineering, 2025)

Evaluation of entomopathogenic fungi and nematode species for eco-friendly management of fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - Usama Saleem; Muhammad Asrar; Dilbar Hussain; Faisal Hafeez; Muhammad Sohail Qadir (International Journal of Tropical Insect Science, 2025)

Exploration of biochars for enhancing soil health, carbon sequestration, and greenhouse gas emission reductions under citrus cultivation - Muhammad Qasim; Saba Babar; Muhammad Usama Younas; Nimra Rajput; Xiaoyang Xia; Jiyuan Wang; Xiangling Wang; Cuncang Jiang (European Journal of Agronomy, 2025)

Experimental study of unglazed transpired solar collectors integrated with buildings in humid sub-tropics - Tariq Talha; Muhammad Talha; Shuli Liu; Abdur Rehman Mazhar; Usama Perwez; Muhammad Moiz; Ahtasham Afzal (Energy and Buildings, 2025)

Investigation of lassa fever with relapse and saturated incidence rate: mathematical modeling and control - Aqeel Ahmad; Usama Atta; Muhammad Farman; Kottakkaran Sooppy Nisar; Hijaz Ahmad; Evren Hincal (Modeling Earth Systems and Environment, 2025)

Integrated Management of Nitrogen and Spent Mushroom Compost for Improved Wheat Yield and Soil Fertility - Uzair Ahmed; Aftab Jamal; Waleed Iqbal; Durrishahwar; Usama Qayyum; Muhammad Farhan Saeed; Amjad Ali; Domenico Ronga; Yaser Hassan Dewir; Jakub Černý (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Enhancing vegetation cover growth through water spreading bunds and dry afforestation in arid rangelands: Integrating remote sensing indicators with field insights - Sawaid Abbas; Aqeela Mobeen Akhter; Muhammad Mushtaque; Raja Muhammad Usama; Ansir Rasool; Muhammad Umar; Muhammad Uzair Mahmood; Marryam Malik (Science of The Total Environment, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Technical and economic assessment of hydrogen production from heavy fuel oil via thermochemical conversion routes - Ali A. Al-Qadri; Usama Ahmed; Shaikh Abdur Razzak; Muhammad Shahbaz; Murid Hussain; Sharif H Zein (Fuel, 2025)

Bacillus subtilis (NMCC-path-14) ameliorates acute phase of arthritis via modulating NF-κB and Nrf-2 signaling in mice model - Muhammad Usama Mazhar; Sadaf Naz; Tayyaba Zulfiqar; Jehan Zeb Khan; Fahim Hilal; Shakira Ghazanfar; Muhammad Khalid Tipu (Inflammopharmacology, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

UBEM-SER: Role of sufficiency, efficiency and renewable in the decarbonization of commercial building stock at city scale - Usama Perwez; Muhammad Haseeb Rasool; Imran Aziz; Usman Zia (Sustainable Cities and Society, 2025)

RETRACTED ARTICLE: Impact of elevated temperatures on the genetic and morpho-physiological traits of cotton genotypes cultivation - Aamir Ali Abro; Muhammad Qasim; Muhammad Usama Younas; Ijaz Ali; Mubashir Abbas; Noor Muhammad; Shiguftah Khalid; Junaid Ahmed; Umbreen Bibi; Muhammad Waqas; Sezai Ercisli; Fahad Al-Asmari; et al. (Genetic Resources and Crop Evolution, 2025)

Microplastic contamination in commercial food and drink products and associated risk of potential human intake in Riyadh, Saudi Arabia - Munir Ahmad; Jahangir Ahmad; Muhammad Usama; Hamed Ahmed Al-Swadi; Mohammed Awad Mousa; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. F. Al-Farraj (Environmental Monitoring and Assessment, 2025)

Do structural and functional traits modulation determine the ecological fate of castor bean (Ricinus communis L.) under variable pedospheric and atmospheric conditions? - Ummar Iqbal; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (South African Journal of Botany, 2025)

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

RETRACTED ARTICLE: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2025)

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Environmental assessment of cenosphere and GGBFS-based geopolymers: A path to greener construction materials - Muhammad Usama Salim; Aamar Danish; Anthony S. Torres; Carlos Moro (Environmental Impact Assessment Review, 2025)

Unveiling the biosorption performance of silk fibroin fiber for Pb(II) and Cr(VI) removal: Machine learning and DFT analysis - Muhammad Usman Farooq; Hammad Khan; Muhammad Arshad; Muhammad Usama; Mohammad Ilyas Khan; Sajjad Hussain; Ali Hamid (Journal of Water Process Engineering, 2024)

RETRACTED ARTICLE: Exploring the molecular mechanisms of rice blast resistance and advances in breeding for disease tolerance - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Xiaohong Jiang; Shimin Zuo (Molecular Biology Reports, 2024)

Allelic variation in rice blast resistance: a pathway to sustainable disease management - Muhammad Usama Younas; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Rashid Iqbal; Ashraf M.M. Abdelbacki; Nimra Rajput; Xiaohong Jiang; Bisma Rao; Shimin Zuo (Molecular Biology Reports, 2024)

Efficacy and safety of ticagrelor monotherapy following a brief DAPT vs. prolonged 12-month DAPT in ACS patients post-PCI: a meta-analysis of RCTs - Usama Qamar; Farhan Naeem; Muhammad Talha Maqsood; Maleeka Zamurad Khan; Zeeshan Imtiaz; Fatima Saeed; Neelesh Gupta; Fnu Zafarullah Brohi; Celestine Mkpozi; Yasar Sattar (European Journal of Clinical Pharmacology, 2024)

Optimizing plastic waste inclusion in paver blocks: Balancing performance, environmental impact, and cost through LCA and economic analysis - Usama Asif; Muhammad Faisal Javed (Journal of Cleaner Production, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Prediction of Monthly Flow Regimes Using the Distance-Based Method Nested with Model Swapping - Muhammad Uzair Qamar; Cuauhtémoc Tonatiuh Vidrio-Sahagún; Jianxun He; Usama Tariq; Akbar Ali (Water Resources Management, 2024)

Adsorptive removal of cationic dyes from wastewater using a novel sodium alginate-based iron oxide nanocomposite hydrogel: DFT and advanced statistical physics modelling - Muhammad Umar; Muhammad Usman Farooq; Muhammad Arshad; Muhammad Usama; Feryal Akbal; Sajjad Hussain; Hammad Khan (Process Safety and Environmental Protection, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Effect of bacillus strain and Fe-modified biochar on lead (Pb) bioaccumulation and oxidative stress in wheat (Triticum aestivum L.) grown in Pb contaminated soil - Sana Noreen; Zaffar Malik; Muhammad Luqman; Ishrat Fatima; Usama Ali Tahir; Mansab Dar; Muhammad Rizwan (South African Journal of Botany, 2024)

In vivo evaluation of efficacy and safety of Coagulansin-A in treating arthritis - Sadaf Naz; Muhammad Usama Mazhar; Sidra Faiz; Maria Nawaz Malik; Jehan Zeb Khan; Ihsan Ul Haq; Lin Zhu; Muhammad Khalid Tipu (Toxicology and Applied Pharmacology, 2024)

Hope or hype? Evaluating the environmental footprint of reclaimed fly ash in geopolymer production - Aamar Danish; Anthony S. Torres; Carlos Moro; Muhammad Usama Salim (Resources, Conservation and Recycling, 2024)

Immunostimulant, hepatoprotective, and nephroprotective potential of Bacillus subtilis (NMCC-path-14) in comparison to dexamethasone in alleviating CFA-induced arthritis - Muhammad Usama Mazhar; Sadaf Naz; Tayyaba Zulfiqar; Jehan Zeb Khan; Shakira Ghazanfar; Muhammad Khalid Tipu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Anti-inflammatory and anti-arthritic potential of Coagulansin-A: in vitro and in vivo studies - Sadaf Naz; Muhammad Usama Mazhar; Umakant Yadav; Hamdy Abouzeid Ali; Fadi Khasawneh; Ihsan-ul-Haq; Muhammad Khalid Tipu; Lin Zhu (Inflammopharmacology, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Generative vs. Non-Generative Models in Engineering Shape Optimization - Zahid Masood; Muhammad Usama; Shahroz Khan; Konstantinos Kostas; Panagiotis D. Kaklis (Journal of Marine Science and Engineering, 2024)
Generative models offer design diversity but tend to be computationally expensive, while non-generative models are computationally cost-effective but produce less diverse and often invalid designs. However, the limitations of non-generative models can be overcome with the introduction of augmented shape signature vectors (SSVs) to represent both geometric and physical information. This recent advancement has inspired a systematic comparison of the effectiveness and efficiency of generative and non-generative models in constructing design spaces for novel and efficient design exploration and shape optimization, which is demonstrated in this work. These models are showcased in airfoil/hydrofoil design, and a comparison of the resulting design spaces is conducted in this work. A conventional generative adversarial network (GAN) and a state-of-the-art generative model, the performance-augmented diverse generative adversarial network (PaDGAN), are juxtaposed with a linear non-generative model based on the coupling of the Karhunen–Loève Expansion and a physics-informed shape signature vector (SSV-KLE). The comparison demonstrates that, with an appropriate shape encoding and a physics-augmented design space, non-generative models have the potential to cost-effectively generate high-performing valid designs with enhanced coverage of the design space. In this work, both approaches were applied to two large foil profile datasets comprising real-world and artificial designs generated through either a profile-generating parametric model or a deep-learning approach. These datasets were further enriched with integral properties of their members’ shapes, as well as physics-informed parameters. The obtained results illustrate that the design spaces constructed by the non-generative model outperform the generative model in terms of design validity, generating robust latent spaces with no or significantly fewer invalid designs when compared to generative models. The performance and diversity of the generated designs were compared to provide further insights about the quality of the resulting spaces. These findings can aid the engineering design community in making informed decisions when constructing design spaces for shape optimization, as it has been demonstrated that, under certain conditions, computationally inexpensive approaches can closely match or even outperform state-of-the art generative models.

Harnessing probiotics and prebiotics as eco-friendly solution for cleaner shrimp aquaculture production: A state of the art scientific consensus - Muhammad Noman; Syed Shabi Ul Hassan Kazmi; Hafiz Sohaib Ahmed Saqib; Usama Fiaz; Paolo Pastorino; Damià Barcelò; Muhammad Tayyab; Wenhua Liu; Zhen Wang; Zaher Mundher Yaseen (Science of The Total Environment, 2024)

Sheep bone valorization: Enhancing gastronomic sustainability through hydroxyapatite-enriched potato wedges - Saba Liaqat; Zaheer Ahmed; Muhammad Usama Umer; Qasim Ali; Muhammad Farooq Mustafa; Ifra Ferheen; Muhammad Waseem (International Journal of Gastronomy and Food Science, 2024)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

A review on identification characters and IPM of wheat aphid by using non-conventional methods - Dilbar Hussain; Usama Saleem; Muhammad Asrar; Muhammad Saleem; Abdul Ghaffar; Saddam Hussain; Tayybah Shaheen; Mubshar Saleem (International Journal of Tropical Insect Science, 2024)

The Influence of Pyrolysis Temperature on the Performance of Cotton Stalk Biochar for Hexavalent Chromium Removal from Wastewater - Usama Khalid; Muhammad Ali Inam (Water, Air, & Soil Pollution, 2024)

Chimaphila umbellata; a biotechnological perspective on the coming-of-age prince’s pine - Urooj Ali; Muhammad Mustajab Khan; Naveera Khan; Rida tul Haya; Muhammad Usama Asghar; Bilal Haider Abbasi (Phytochemistry Reviews, 2024)

Silica-embedded nutrient-doped biochar improves nutrient availability and safflower (Carthamus tinctorius L.) growth in cadmium- and lead-contaminated soil - Munir Ahmad; Hamed Ahmed Al-Swadi; Jahangir Ahmad; Muhammad Usama; Mohammed Awad Mousa; Nahrir M. A. Lubis; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. Al-Farraj (Journal of Soils and Sediments, 2024)

Efficacy of Green Synthesized Silver Based Nanomaterials Against Early Blight of Tomato Caused by Alternaria solani - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Shahbaz Talib Sahi; Mohsin Shad; Nian Lili; Shahid Iqbal; Asif Mahmood Arif; Usama Ahmad; Khurram Shehzad Khan; Muhammad Asif; Fasih Ullah Haider (Journal of Crop Health, 2024)

Recent outbreak of Marburg virus; a global health concern and future perspective - Usama Mujahid; Muhammad Ahmad; Attiqa Mujahid; Edward Narayan; Saif Ur Rehman; Hafiz M. N. Iqbal; Ishtiaq Ahmed (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Feeding ethogram of Antilochus coquebertii F. preying on Dysdercus koenigii - Adeel Mukhtar; Muhammad Usama Altaf; Muhammad Ikhlaq; Waqar Jaleel; Syed Muhammad Zaka; Asad Ali; Zahid Hanif (Journal of Asia-Pacific Entomology, 2023)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

Sustainable wastewater purification with crab shell-derived biochar: Advanced machine learning modeling & experimental analysis - Amina Bibi; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Fazal Wahab; Muhammad Usama; Khurram Khan; Feryal Akbal (Bioresource Technology, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

Inheritance of esterases based spiromesifen resistance in Musca domestica Linnaeus (Diptera: Muscidae) - Hafiz Muhammad Usama Khan; Rizwan Mustafa Shah; Sarfraz Ali Shad (International Journal of Tropical Insect Science, 2023)

Scavenging microplastics and heavy metals from water using jujube waste-derived biochar in fixed-bed column trials - Munir Ahmad; Nahrir M.A. Lubis; Muhammad Usama; Jahangir Ahmad; Mohammad I. Al-Wabel; Hamed A. Al-Swadi; Muhammad Imran Rafique; Abdullah S.F. Al-Farraj (Environmental Pollution, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Single Pot Enzymatic Treatment of Sugarcane Bagasse Using Laccase and Cellulase for the Production of Value-Added Products - Usama Hafeez; Muhammad Sohail; Syed Tariq Ali (Sugar Tech, 2023)

Hydrological response under CMIP6 climate projection in Astore River Basin, Pakistan - Zeshan Ali; Mudassar Iqbal; Ihsan Ullah Khan; Muhammad Umer Masood; Muhammad Umer; Muhammad Usama Khan Lodhi; Muhammad Atiq Ur Rehman Tariq (Journal of Mountain Science, 2023)
Climate change strongly influences the available water resources in a watershed due to direct linkage of atmospheric driving forces and changes in watershed hydrological processes. Understanding how these climatic changes affect watershed hydrology is essential for human society and environmental processes. Coupled Model Intercomparison Project phase 6 (CMIP6) dataset of three GCM’s (BCC-CSM2-MR, INM-CM5-0, and MPI-ESM1-2-HR) with resolution of 100 km has been analyzed to examine the projected changes in temperature and precipitation over the Astore catchment during 2020–2070. Bias correction method was used to reduce errors. In this study, statistical significance of trends was performed by using the Man- Kendall test. Sen’s estimator determined the magnitude of the trend on both seasonal and annual scales at Rama Rattu and Astore stations. MPI-ESM1-2-HR showed better results with coefficient of determination (COD) ranging from 0.70–0.74 for precipitation and 0.90–0.92 for maximum and minimum temperature at Astore, Rama, and Rattu followed by INM-CM5-0 and BCC-CSM2-MR. University of British Columbia Watershed model was used to attain the future hydrological series and to analyze the hydrological response of Astore River Basin to climate change. Results revealed that by the end of the 2070s, average annual precipitation is projected to increase up to 26.55% under the SSP1–2.6, 6.91% under SSP2–4.5, and decrease up to 21.62% under the SSP5–8.5. Precipitation also showed considerable variability during summer and winter. The projected temperature showed an increasing trend that may cause melting of glaciers. The projected increase in temperature ranges from - 0.66°C to 0.50°C, 0.9°C to 1.5°C and 1.18°C to 2°C under the scenarios of SSP1–2.6, SSP2–4.5 and SSP5–8.5, respectively. Simulated streamflows presented a slight increase by all scenarios. Maximum streamflow was generated under SSP5–8.5 followed by SSP2–4.5 and SSP1–2.6. The snowmelt and groundwater contributions to streamflow have decreased whereas rainfall and glacier melt components have increased on the other hand. The projected streamflows (2020–2070) compared to the control period (1990–2014) showed a reduction of 3%–11%, 2%–9%, and 1%–7% by SSP1–2.6, SSP2–4.5, and SSP5–8.5, respectively. The results revealed detailed insights into the performance of three GCMs, which can serve as a blueprint for regional policymaking and be expanded upon to establish adaption measures.

Assessment of lead, cadmium, and mercury levels in the breast milk in Pakistani women - Naveed Ahmad; Abbas Muhammad; Ramna Zafar; Usama Afzal; Muhammad Aslam (Environmental Science and Pollution Research, 2023)

An approach to assess offshore wind power potential using bathymetry and near-hub-height reanalysis data - Zia ul Rehman Tahir; Muhammad Abdullah; Sajeer Ahmad; Ammara Kanwal; Muhammad Farhan; Usama Bin Saeed; Tariq Ali; Imran Amin (Ocean Engineering, 2023)

Synthesis and two-step KOH based activation of porous biochar of wheat straw and waste tire for adsorptive exclusion of chromium (VI) from aqueous solution; thermodynamic and regeneration study - Usama Jamil; Muhammad Zeeshan; Shoaib Raza Khan; Sara Saeed (Journal of Water Process Engineering, 2023)

Potential Breeding Strategies for Improving Salt Tolerance in Crop Plants - Muhammad Afzal; Salah El Sayed Hindawi; Salem Safer Alghamdi; Hussein H. Migdadi; Muhammad Altaf Khan; Muhammad Usama Hasnain; Muhammad Arslan; Muhammad Habib ur Rahman; Muhammad Sohaib (Journal of Plant Growth Regulation, 2023)
Salinity is one of the significant abiotic stresses that negatively affect plant production processes, growth, and development, which ultimately reduce yield. Plants adapt specific mechanisms to withstand saline conditions and activate diverse salt tolerance genes to counter osmotic and oxidative stresses induced by salinity. Genetic development in salinity tolerance is quite complex, while advancement has made less progress than expectation over the past few decades. Generating an explosion of genetics- and genomics-related information and technology in recent decades pledge to deliver innovative and advanced resources for the potential production of tolerant genotypes. Despite considerable progress in defining the primary salinity tolerance mechanisms, main obstacles are yet to be solved in the translation and incorporation of the resulting molecular knowledge into the plant breeding activities. Diverse approaches are proposed to enhance plant breeding efficacy to increase plant productivity in saline environments. Understanding the genetics of salt tolerance is a difficult task because multiple genes and pathways are involved. Important advances in tools and methods for updating and manipulating plant genomics knowledge provide detailed insights and dissect the salinity tolerance mechanism accomplished by the breeding goals. Genome-wide analyses (GWA) identify SNP variations and functional effects that appear to be the way of the future for developing salinity-tolerant plants. Gene discovery to manipulate the molecular mechanisms which underlie the complex phenotype of salinity tolerance methods, identification of genes, QTL, association mapping, linkage, and functional genomics, such as transcript identifying and proteins related to salinity, is necessary. The present analysis also discussed some of the opportunities and challenges, focusing on molecular breeding strategies used in conjunction with other crop development approaches to growing elite salt-tolerant lines.

Integrating wheat straw and silica fume as a balanced mechanical ameliorator for expansive soil: a novel agri-industrial waste solution - Usama Khalid; Zia ur Rehman; Nauman Ijaz; Inamullah Khan; Muhammad Faisal Junaid (Environmental Science and Pollution Research, 2023)

Remediation methods of heavy metal contaminated soils from environmental and geotechnical standpoints - Zia ur Rehman; Muhammad Faisal Junaid; Nauman Ijaz; Usama Khalid; Zain Ijaz (Science of The Total Environment, 2023)

Production of fuel oil from elastomer rubber waste via methanothermal liquefaction - Nabeel Ahmad; Nauman Ahmad; Usama Ahmed; Abdul Gani Abdul Jameel; Um-e-Salma Amjad; Murid Hussain; Muhammad Maaz Arif (Fuel, 2023)

High pressure CO2 adsorption onto Malaysian Mukah-Balingian coals: Adsorption isotherms, thermodynamic and kinetic investigations - Mustafa Abunowara; Mohamad Azmi Bustam; Suriati Sufian; Muhammad Babar; Usama Eldemerdash; Ahmad Mukhtar; Sami Ullah; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Su Shiung Lam (Environmental Research, 2023)

The mechanism of alkali-aggregate reaction in concrete/mortar and its mitigation by using geopolymer materials and mineral admixtures: a comprehensive review - Muhammad Usama Salim; Mohammad Ali Mosaberpanah (European Journal of Environmental and Civil Engineering, 2022)

Assessment of Climate Change and Its Impacts on the Flows of a Subtropical River Basin in the Hindu-Kush Mountain, South Asia - Muhammad Naveed Anjum; Abdulnoor A. J. Ghanim; Hafiz Umar Farid; Muhammad Zaman; Usama Muhammad Niazi; Saif ur Rahman; Mabkhoot A. Alsaiari; Muhammad Irfan (Pure and Applied Geophysics, 2022)

Numerical analysis of energy dissipator options using computational fluid dynamics modeling — a case study of Mirani Dam - Usama Majeed; Najam us Saqib; Muhammad Akbar (Arabian Journal of Geosciences, 2022)

Effects of dam on temperature, humidity and precipitation of surrounding area: a case study of Gomal Zam Dam in Pakistan - Jamil Afzal; Zhou Yihong; Maria Qayum; Usama Afzal; Muhammad Aslam (Environmental Science and Pollution Research, 2022)

Eco-friendly acid dyeing of silk and wool fabrics using Acid Violet 49 dye - Muhammad Usama Shabbir; Shahid Adeel; Tanveer Hussain Bokhari; Muhammad Usman; Muhammad Kaleem Khosa; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Intelligent Diagnosis of Fish Behavior Using Deep Learning Method - Usama Iqbal; Daoliang Li; Muhammad Akhter (Fishes, 2022)
Scientific methods are used to monitor fish growth and behavior and reduce the loss caused by stress and other circumstances. Conventional techniques are time-consuming, labor-intensive, and prone to accidents. Deep learning (DL) technology is rapidly gaining popularity in various fields, including aquaculture. Moving towards smart fish farming necessitates the precise and accurate identification of fish biodiversity. Observing fish behavior in real time is imperative to make better feeding decisions. The proposed study consists of an efficient end-to-end convolutional neural network (CNN) classifying fish behavior into the normal and starvation categories. The performance of the CNN is evaluated by varying the number of fully connected (FC) layers with or without applying max-pooling operation. The accuracy of the detection algorithm is increased by 10% by incorporating three FC layers and max pooling operation. The results demonstrated that the shallow architecture of the CNN model, which employs a max-pooling function with more FC layers, exhibits promising performance and achieves 98% accuracy. The presented system is a novel step in laying the foundation for an automated behavior identification system in modern fish farming.

Effect of slow release nitrogenous fertilizers and biochar on growth, physiology, yield, and nitrogen use efficiency of sunflower under arid climate - Muhammad Waqar; Muhammad Habib-ur-Rahman; Muhammad Usama Hasnain; Shahid Iqbal; Abdul Ghaffar; Rashid Iqbal; Muhammad Iftikhar Hussain; Ayman EL Sabagh (Environmental Science and Pollution Research, 2022)
Sunflower plants need nitrogen consistently and in higher amount for optimum growth and development. However, nitrogen use efficiency (NUE) of sunflower crop is low due to various nitrogen (N) losses. Therefore, it is necessary to evaluate the advanced strategies to minimize N losses and also improve sunflower productivity under arid climatic conditions. A field trial was conducted with four slow release nitrogenous fertilizers [SRNF (bacterial, neem, and sulfur-coated urea and N loaded biochar)] and three N levels (100% = 148 kg N ha −1 , 80% = 118 kg N ha −1 , and 60% = 89 kg N ha −1 ) of recommended application (100%) for sunflower crop under arid climatic conditions. Results showed that neem-coated urea at 148 kg N ha −1 significantly enhanced crop growth rate (CGR) (19.16 g m −2 d −1 ) at 60–75 days after sowing (DAS); leaf area index (2.12, 3.62, 5.97, and 3.00) at 45, 60, 75, and 90 DAS; and total dry matter (14.27, 26.29, 122.67, 410, and 604.33 g m −2 ) at 30, 45, 60, 75, and 90 DAS. Furthermore, higher values of net leaf photosynthetic rate (25.2 µmol m −2 s −1 ), transpiration rate (3.66 mmol s −1 ), and leaf stomatal conductance (0.39 mol m −2 s −1 ) were recorded for the same treatment. Similarly, neem-coated urea produced maximum achene yield (2322 kg ha −1 ), biological yield (9000 kg ha −1 ), and harvest index (25.8%) of the sunflower crop. Among various N fertilizers, neem-coated urea showed maximum NUE (20.20 kg achene yield kg −1 N applied) in comparison to other slow release N fertilizers. Similarly, nitrogen increment N 60 showed maximum NUE (22.40 kg grain yield kg −1 N applied) in comparison to N 80 and N 100 . In conclusion, neem-coated urea with 100% and 80% of recommended N would be recommended for farmers to get better sunflower productivity with sustainable production and to reduce the environmental nitrogen losses.

A New Sequential Forward Feature Selection (SFFS) Algorithm for Mining Best Topological and Biological Features to Predict Protein Complexes from Protein–Protein Interaction Networks (PPINs) - Haseeb Younis; Muhammad Waqas Anwar; Muhammad Usman Ghani Khan; Aisha Sikandar; Usama Ijaz Bajwa (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Adoption of green IT in Pakistan: a comparison of three competing models through model selection criteria using PLS-SEM - Saqib Ali; Hafiz Muhammad Usama Javed; Muhammad Danish (Environmental Science and Pollution Research, 2021)

Rainfall reconstruction for the Karakoram region in Pakistan since 1540 CE reveals out‐of‐phase relationship in rainfall between the southern and northern slopes of the Hindukush‐Karakorum‐Western Himalaya region - Adam Khan; Feng Chen; Moinuddin Ahmed; Muhammad Usama Zafar (International Journal of Climatology, 2020)
Climate change has influenced the glaciers and water resources in the Hindukush‐Karakorum‐Himalaya region. The relatively short instrumental record of northern Pakistan makes long‐term climate change assessments difficult. In this paper, tree‐ring width chronologies were developed from two stands of spruce species ( Picea smithiana ) in the Karakoram region of northern Pakistan. The results of the correlation analysis revealed that tree‐ring growth of spruce was limited by annual (June–May) precipitation. Based on the regional chronology, we developed an annual precipitation reconstruction for the period 1540–2016 CE. The precipitation reconstruction equation accounts for 40% of the regional precipitation variance during the instrumental period 1946–2016. Dry episodes with rainfall below the 477‐year average occurred from 1569 to 1577, 1598 to 1612, 1621 to 1621, 1638 to 1654, 1673 to 1680, 1697 to 1720, 1728 to 1739, 1753 to 1761, 1777 to 1793, 1801 to 1840, 1860 to 1874, 1914 to 1932, 1960 to 1985, 1998 to 2011. Wet episodes occurred from 1540 to 1568, 1578 to 1597, 1613 to 1620, 1632 to 1637, 1655 to 1672, 1681 to 1696, 1721 to 1727, 1740 to 1752, 1762 to 1776, 1794 to 1800, 1841 to 1859, 1875 to 1913, 1933 to 1959, 1986 to 1997. Furthermore, the results of spatial correlation analyses show that the reconstructed precipitation represents the regional precipitation variations for northern Pakistan and nearby high‐altitude mountains. The out‐of‐phase relationship in tree‐ring records of the Karakoram region and surrounding areas suggests that the Karakoram was under the control of large‐scale ocean–atmosphere–land circulations on a decadal timescale in the past centuries. In addition, by the comparison between the precipitation reconstruction and the instrumental data, we found that the drought risk of Karakoram has increased in the past 70 years and that extreme events are likely to become more severe and more frequent under the backdrop of climatic warming.

A comprehensive study on the surface chemistry of particulate matter collected from Jeddah, Saudi Arabia - Asim Jilani; Syed Zajif Hussain; Mohd Hafiz Dzarfan Othman; Usama Zulfiqar; Muhammad Bilal Shakoor; Imran Ullah Khan; Javed Iqbal; Attieh A. Al-Ghamdi; Ahmed Alshahrie (Journal of Atmospheric Chemistry, 2018)

The impact of biomass energy consumption on pollution: evidence from 80 developed and developing countries - Sakiru Adebola Solarin; Usama Al-Mulali; Gerald Goh Guan Gan; Muhammad Shahbaz (Environmental Science and Pollution Research, 2018)

Dynamic linkages among energy consumption, air pollution, greenhouse gas emissions and agricultural production in Pakistan: sustainable agriculture key to policy success - Muhammad Imran Qureshi; Usama Awan; Zeeshan Arshad; Amran Md. Rasli; Khalid Zaman; Faisal Khan (Natural Hazards, 2016)

Karakorum temperature out of phase with hemispheric trends for the past five centuries - Muhammad Usama Zafar; Moinuddin Ahmed; Mukund Palat Rao; Brendan M. Buckley; Nasrullah Khan; Muhammad Wahab; Jonathan Palmer (Climate Dynamics, 2016)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

POM analyses of antimicrobial activity of some 2,3-armed 4,5,6,7-tetrahydro-1-benzothiophenes: favourable and unfavourable physico-chemical parameters in design of antibacterial and mycolytic agents - Taibi Ben Hadda; Sajal Srivastava; Barnali Das; Héctor Salgado-Zamora; Usama Shaheen; Ammar Bader; Muhammad Moazzam Naseer (Medicinal Chemistry Research, 2014)

Methionine+cystine requirement of broiler chickens fed low-density diets under tropical conditions - Usama Aftab; Muhammad Ashraf (Tropical Animal Health and Production, 2009)